The economic and economic statistical designs of synthetic double sampling X‾ chart. Issue 8 (14th September 2019) - Lee, Ming Ha; Khoo, Michael B. C.
ABSTRACT: The purpose of this paper is to investigate the economic and economic statistical designs of the synthetic double sampling (DS) X ‾ chart. The optimal design parameters for the economic design are determined such that the cost is minimized for the given cost model parameters. For the economic statistical design, the cost is minimized subject to statistical constraint. The numerical comparison demonstrates that the synthetic DS X ‾ chart is economically superior to the synthetic and DS X ‾ charts. A sensitivity analysis is conducted to study the effect of the cost model parameters on the solution for the economic statistical design.